2007
DOI: 10.3324/haematol.10752
|View full text |Cite
|
Sign up to set email alerts
|

The potential effect of gender in combination with common genetic polymorphisms of drug-metabolizing enzymes on the risk of developing acute leukemia

Abstract: Background and ObjectivesWe examined common polymorphisms in the genes for glutathione S-transferase (GST), cytochrome P450 (CYP), quinone oxoreductase (NQO1), methylene tetrahydrofolate reductase (MTHFR), and thymidylate synthetase (TYMS) and the role of gender associated with the susceptibility to de novo acute leukemia (AL). Design and MethodsWe conducted a case-control study analyzing the prevalence of the polymorphisms CYP1A1*2A, CYP2E1*5B, CYP3A4*1B, del{GSTT1}, del{GSTM1}, NQO1*2, MTHFR C6777, and TYMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 30 publications
6
42
0
Order By: Relevance
“…On the contrary, Liu et al 21 concluded that RAD51 gene polymorphism was significantly related to response to therapy, adverse effects, and prognosis of AML and reported that the detection of the RAD51 gene polymorphism genotypes may be useful in selecting individual chemotherapy regimens for patients with AML. Also, Bolufer et al 22 reported that the RAD51 gene polymorphism showed significant unfavorable outcome among AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Liu et al 21 concluded that RAD51 gene polymorphism was significantly related to response to therapy, adverse effects, and prognosis of AML and reported that the detection of the RAD51 gene polymorphism genotypes may be useful in selecting individual chemotherapy regimens for patients with AML. Also, Bolufer et al 22 reported that the RAD51 gene polymorphism showed significant unfavorable outcome among AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, quinone oxoreductase*2 homozygosity is associated in males below 30 or over 50 years of age with the AML M3 FAB subtype but not in females. 42 The gender difference in AML is lowest in the age group 30-50 years. This might be one explanation why men have a higher risk to develop AML, depending on age.…”
Section: Metabolismmentioning
confidence: 99%
“…In addition to carcinogen exposure, an individual's unique immune system, diet, and genetic polymorphisms may play a role in susceptibility to developing acute leukemia. It has been proposed that gender, in combination with polymorphisms, may affect the risk of acquiring acute leukemia, since researchers have found that males with the NQO1*2 homozygous and del(GSTT1) polymorphisms are at a higher risk of acquiring acute leukemia than females with these polymorphisms [26].…”
Section: Discussionmentioning
confidence: 99%